2016
DOI: 10.1080/03670244.2016.1150276
|View full text |Cite
|
Sign up to set email alerts
|

Does the rise in eating disorders lead to increasing risk of orthorexia nervosa? Correlations with gender, education, and body mass index

Abstract: Investigating eating disorders and orthorexia nervosa, especially in the young population, is an important step in taking protective precautions and identifying disease. This study was carried out to determine the relationship of eating disorders and orthorexia nervosa to gender, BMI, and field of study in a population of university students in Turkey. In all, 900 university students aged 17-23 years participated in this study. EAT-40 and ORTO-15, which are validated instruments for the screening of participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
45
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 28 publications
14
45
2
7
Order By: Relevance
“…Our results do not confirm those of other researchers reporting a significant relationship between less orthorexic traits and less level of eating pathology among American students (r = -0.26, p \ 0.01) [18] and Turkish students (r = -0.40, p \ 0.001) [45]. It is worth pointing out that there is one previous study supporting our results [46], although the authors used the Orthorexia Self-Test, commonly named as the Bratman Orthorexia Test (BOT). The authors report a significant positive correlation between total BOT and EAT-26 scores (r = 0.47, p \ 0.01) [46].…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Our results do not confirm those of other researchers reporting a significant relationship between less orthorexic traits and less level of eating pathology among American students (r = -0.26, p \ 0.01) [18] and Turkish students (r = -0.40, p \ 0.001) [45]. It is worth pointing out that there is one previous study supporting our results [46], although the authors used the Orthorexia Self-Test, commonly named as the Bratman Orthorexia Test (BOT). The authors report a significant positive correlation between total BOT and EAT-26 scores (r = 0.47, p \ 0.01) [46].…”
contrasting
confidence: 99%
“…It is worth pointing out that there is one previous study supporting our results [46], although the authors used the Orthorexia Self-Test, commonly named as the Bratman Orthorexia Test (BOT). The authors report a significant positive correlation between total BOT and EAT-26 scores (r = 0.47, p \ 0.01) [46]. Segura-Garcia et al [21], and Herranz Valera et al [47] showed an association between ON and its increased prevalence following eating disorders (ED) improvement, besides they indicated that in ED patients the frequency of orthorexic behaviors increases alongside with the decrease of ED pathology [48].…”
supporting
confidence: 76%
“…According to these premises, we identified three main areas of interest: 1) a deeper understanding of the orthorexia construct, considering its possible and currently debated relation with full-blown eating disorders; 2) the investigation of the personality correlates of orthorexic attitudes and behaviors; 3) the role of the cultural context on orthorexia.Regarding the first area, there is still much inconsistency in the existing literature. A previous study [20] by our research group investigated orthorexia in a sample of patients with a clinical diagnosis of eating disorders, showing that more pathological ON attitudes and behaviors (as measured by the ORTO-15 test) were related to lower degrees of disordered eating (as assessed with the Eating Attitudes Test-26). While another study has supported a negative correlation between ON and disordered eating patterns [21], others (using the Bratman Orthorexia Test and the Eating Habits Questionnaire, respectively) found increased ON features corresponding to more severely disordered eating behaviors (particularly calories restriction and weight concerns) [2].…”
Section: Introductionmentioning
confidence: 84%
“…Last, the interplay between socio-cultural context and ON has been poorly investigated. We already addressed this topic in a previous study [20] involving Italian and Polish females with AN and healthy controls. Less orthorexic features, as assessed with the ORTO-15, emerged in the Italian than in the Polish samples (both AN and healthy control group).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that the ORTO-15 and EAT-40 correlate. 22,29 Here, the D-ON and D-ED groups had higher scores for every subscale of the EDE-Q6 than the D-HC group, demonstrating that ON involves not only the expected associations related to eating choices (assessed in the EDE-Q, eating concern) and control (EDE-Q, restraint) but also includes cognitive preoccupations about body shape (EDE-Q, shape) and weight (EDE-Q, weight).…”
Section: Discussionmentioning
confidence: 99%